KETERAMPILAN GURU DALAM PEMBUATAN MEDIA PEMBELAJARAN MEMBACA PERMULAAN DI SDN LIALANG KOTA SERANG - Muhamad Ainun Najib; Sayidatul Fariha (Universitas Islam Malang, 2023)
In the learning, planning and preparation of learning is very important, the use of appropriate media can support the achievement of learning objectives, so that learning is expected to go according to what was planned. This research was conducted to determine the skills of teachers in making learning media for beginning reading at SDN Lialang, Serang City. The approach used in this study is a descriptive qualitative approach. The research data comes from observations, interviews with relevant sources and document studies. Based on the results of research conducted by the teacher's skills in making beginning reading learning media at SDN Lialang, Serang city, it has increased along with the obstacles faced, some of the creations of learning media are made from used materials which are reused as learning media, such as letter cards and reading book.